A Replay Attack Against ISAC Based on OFDM - Georgios Chrysanidis; Yanwei Liu; Antonios Argyriou (IEEE Access, 2024)
Integrated sensing and communication (ISAC) is envisioned to be a core element of future 6G and connected vehicular wireless systems. As always wireless security and privacy will still be of outmost importance. Existing research on ISAC has not explored sufficiently security attacks that compromise its sensing operation. In this paper we present a new wireless range-Doppler replay attack that can compromise the functionality of ISAC systems that use orthogonal frequency division multiplexing (OFDM) for sensing and data communication. With the proposed attack the adversary detects wireless OFDM transmissions and retransmits the same wireless frame (preamble and data) but with a phase shift that varies across subcarriers and successive OFDM symbols of the frame. This results in the creation of false targets in the range-Doppler images that are created by the ISAC system. Our simulation results for a vehicular scenario show that the ISAC system cannot distinguish the false targets from the real ones even when the attacker uses low transmission power. The implication of this attack is that it may lead to inability of advanced driver assistance systems (ADAS) or connected autonomous vehicular (CAV) systems that use ISAC to operate safely.